1992
DOI: 10.1007/bf03008717
|View full text |Cite
|
Sign up to set email alerts
|

Reconstituted thiopentone retains its alkalinity without bacterial contamination for up to four weeks

Abstract: The manufacturers of thiopentone recommend that after reconstitution, it should be kept only for 24 hr to reduce the risk of contamination. However, there are no studies to support this practice and compliance with this recommendation has economic implications. The reasons for discarding a reconstituted bottle of thiopentone are related to concerns about chemical and physical (pH) stability, contamination with infectious agents, and contamination with cellular material. We studied the incidence of bacterial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 13 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…In previous studies, antimicrobial effects of various sedative agents have been studied, but the mechanism underlying their antibacterial activity has not been fully understood. Several studies found that the antimicrobial effects of some of the sedative agents may depend on their molecular weight, pH, and thermodynamic activity (12)(13)(14). A number of researchers revealed the interaction between the cytoplasmic membrane and macromolecule, through which the agents can alter membrane functions by decreasing the number of viable cells and causing the lysis of protoplasts, thus changing the permeability (12).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, antimicrobial effects of various sedative agents have been studied, but the mechanism underlying their antibacterial activity has not been fully understood. Several studies found that the antimicrobial effects of some of the sedative agents may depend on their molecular weight, pH, and thermodynamic activity (12)(13)(14). A number of researchers revealed the interaction between the cytoplasmic membrane and macromolecule, through which the agents can alter membrane functions by decreasing the number of viable cells and causing the lysis of protoplasts, thus changing the permeability (12).…”
Section: Discussionmentioning
confidence: 99%
“…Three positive cultures obtained from different thiopental vials in our study at 24 hours, seven days and 14 days were considered to be the result of survival of organisms washed up on the side or lid of the vial after agitation, or were due to laboratory contamination. Thiopental is frequently used for longer after reconstitution than recommended by the manufactures in many human hospitals (Wong and others 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The pH of propofol and alfaxalone provides a suitable environment for bacterial replication, whereas the strongly alkaline pH of thiopental creates a bactericidal environment for most pathogenic microorganisms. Although reconstituted barbiturates are unstable in solution, Wong and others (1992) showed that even uncapped bottles of 2·5 per cent thiopental maintained their pH for at least four weeks at room temperature. In our study, the three anaesthetic agents were kept at room temperature, although the manufactures of thiopental recommend storage at 2 to 8°C after reconstitution.…”
Section: Discussionmentioning
confidence: 99%
“…• midazolam HCl (Roche)-as supplied 10 mg/ml; 1 mg/ml in normal saline; 1 mg/ml in 5% dextrose • morphine sulphate (David Bull Laboratories)-as supplied 10 mg/ml; 1 mg/ml in normal saline; 1 mg/ml in 5% dextrose • fentanyl citrate (Astra)-as supplied 50 µg/ml; 10 µg/ml in normal saline; 10 µg/ml in 5% dextrose • pethidine HCl (Sigma)-as supplied 50 mg/ml; 10 mg/ml in normal saline; 10 mg/ml in 5% dextrose • bupivacaine HCl (Astra)-as supplied 0.5%; as supplied 0.25%; 0.1% in normal saline. After review of the literature [7][8][9] , the following protocol was followed.…”
Section: Methodsmentioning
confidence: 99%